A web-based skill assessment tool for the Libyan software industry / Yousef Omran Belman - Yousef Omran, Belman (2007)
An explosive growth in the software industry had been seen in the last twenty five years. Now the software market in the world exceeds 370 billion U$ leaded by USA in which software industry sector accounts half of the world software sales followed by Western Europe which accounts the third. Beside developed countries, there are some development countries that develop and expand their software industry and now they accounts for nearly 5 percent of world software sales. Libyan software industry is still in its primary stages and it is not in the position to give Libya the opportunity to compete and cope especially with newly emerged countries. The main objective of this research is to study the current state of the Libyan software industry and to understand its characteristics, current problems and the challenges it has to meet. In order to investigate the status of the Libyan Software Industry, two types of data sources were used, primary and secondary data sources. As a primary source of data, two surveys were conducted to collect the required data for this research. The first survey was the companies’ survey that targeting companies engaged in software development. The second survey directed to the workforce people participating in software development. Both surveys were conducted in Libya. They were submitted and collected by hand. Secondary sources of data were reviewing software related to archival data sources, such as existing organizational documents, researches and reports on other countries’ software industry, software market reports, statistical reports on Libya and other countries and software development related websites. In addition, an Online Skill Assessment Tool (OSAT) was developed as part of this research. It aims to help software companies evaluate their workforce, and to provide statistical information about their skills and recommendations for suggested training plans. OSAT can also be used as a benchmarking tool for the recruitment of software workforce. This is in line with the initiative of software process improvement. The conclusion of this research is that, ad hoc software development is a common practice in local companies. This has contributed to producing low-quality local software. The economic hardship that the country went through has badly affected all aspects of life in Libya including the local software industry. However, there are great opportunities for Libyan software companies to compete especially in Arabic software. The recent national policies are promising factors for local software improvement and competitiveness. The significance of this research is that it can be considered as a pioneer study to investigate the state-of-the-art of local software industry. We expect that it will open up doors for more similar studies. Findings of the study shall be of a greater help to IT policy makers in Libya. In addition OSAT, which in a software competencies management tool shall be greater help for local companies.